Perceived work-related stress and associated factors among the surgical workforce in a Nigerian tertiary health facility: A cross-sectional study. - Jibril M Bashar; Danjuma Aliyu; Emmanuel E Anyebe; Israel Gabriel; Amanullahi Nasir; Abdulrrahaman S Mangari; Faizah S Abubakar; Yusuf H Wada (PLOS Global Public Health)
Healthcare workers continue to experience high levels of work-related stress which continue to negatively affect their psychological, physical, and emotional well-being. This is even more prevalent among healthcare workers who work in surgical specialities, with the surgical operation room becoming a known stressor at hospitals. This study aims to assess work-related stress among surgical team members at Ahmadu Bello University Teaching Hospital in Zaria between January 2021-2022. Data analysis involved descriptive and inferential statistical approaches using the Statistical Package for Social Science (SPSS) version 23.0. The study found an overall high prevalence of work-related stress, with 65% of participants reporting moderate levels of stress. The majority of the participants have a mean age of 39.4 ± 7.8 years, most of them being physicians (66.3%), being males (59.9%), and identified with a Hausa ethnic tribe. Notably, the multiple regression analysis found that tribe (p = 0.008), professional cadres (p = 0.001) and age/years of experience (p = 0.0035) emerged as significant predictors of work-related stress. Key determinants of work-related stress among surgical team members include workload, complexity of work, and conflicting cognitive job demands that continue to subject professionals to increasing workloads and constant decision-making about their job. Organizational factors, such as job policy and procedure, communication problems, and the nature of facilities, were identified as the highest contributors to work-related stress in organizational, interpersonal, and physical/environmental dimensions. The findings lead to the conclusion that a considerable proportion of surgical team members experience a relatively high level of work-related stress, primarily attributed to workload and cognitive demands. In light of these results, urgent efforts are recommended to improve the working conditions and environment for surgical team members. Furthermore, the integration of stress management measures into the educational programs for the surgical team is emphasized to effectively address and mitigate the impact of work-related stress.